2017
DOI: 10.1021/acs.jproteome.7b00334
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathways Regulated by Chitosan Contributing to Drought Resistance in White Clover

Abstract: Increased endogenous chitosan (CTS) could be associated with improved drought resistance in white clover (Trifolium repens). Plants were pretreated with or without 1 mg/mL CTS and then were subjected to optimal or water-limited condition in controlled growth chambers for 6 days. Phenotypic and physiological results indicated that exogenous CTS significantly improved drought resistance of white clover. Metabolome results showed that exogenous CTS induced a significant increase in endogenous CTS content during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 96 publications
4
76
0
Order By: Relevance
“…Multiple previous studies have proven that the maintenance of metabolic balance, the activation of certain metabolic pathways, and the accumulation of specific metabolites are vital defensive and adaptive mechanisms when plants suffer from a harsh environment, such as drought or high temperature (Du et al ; Li et al , , ; Xu et al ). Based on metabonomics, SNP, GABA, and MAS regulated many metabolites and several major metabolic processes in common or differentially, including carbohydrates and amino acids metabolism, TCA cycle, GABA shunt, and other pathways, which could be contributed to SNP‐, GABA‐, and MAS‐induced stress adaptation in white clover (Figures –10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple previous studies have proven that the maintenance of metabolic balance, the activation of certain metabolic pathways, and the accumulation of specific metabolites are vital defensive and adaptive mechanisms when plants suffer from a harsh environment, such as drought or high temperature (Du et al ; Li et al , , ; Xu et al ). Based on metabonomics, SNP, GABA, and MAS regulated many metabolites and several major metabolic processes in common or differentially, including carbohydrates and amino acids metabolism, TCA cycle, GABA shunt, and other pathways, which could be contributed to SNP‐, GABA‐, and MAS‐induced stress adaptation in white clover (Figures –10).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the significant accumulation of galactose and xylose were only observed in MAS‐treated white clover as compared to untreated plants under water stress (Figure ). It has been found that the improved tolerance to water stress was correlated with chitosan‐induced accumulation of galactose and xylose in white clover (Li et al ). The severe drought together with high temperature led to greater increases in glucose and galactose content conferring better OA in poplar ( Populus ) leaves (Jia et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interesting results were obtained using CHT to protect plants against abiotic stresses. CHT (1 mg/mL, origin and characteristics not further specified, viscosity 5−30 mPa s, added 2 days before exposition of plants to dehydration stress) improves drought resistance in white clover (Trifolium repens) by enhancing the accumulation of stress protective metabolites [9]. Foliar application of CHT (200-400 µL/L, origin and characteristics not further specified, sprayed three times, just prior to flowering stage, at 50% flowering and at full bloom) reduces the negative impact of drought condition on dry matter and oil yield of Thymus daenensis Celak [10].…”
Section: Cht Effects On Plant Productivitymentioning
confidence: 99%